Propagation of yellow mombin by stem and root cuttings treated with indolebutyric acid - Neto, Sebastião Elviro de Araújo; Novelli, Dheimy da Silva; Tamwing, Gabriela da Silva; da Silva, Nilciléia Mendes; e Souza, Luis Gustavo de Souza (Comunicata Scientiae, 2019)
Yellow mombin is a fruit species of growing interest in the agro-industrial sector, mainly in the North and Northeast regions of Brazil, although its commercial exploitation is still limited due to the lack of information regarding its propagation, among other factors. In this perspective, this work aimed to study the effect of the application of indolebutyric acid (IBA) in the vegetative propagation of yellow mombin by stem and root cuttings. The experiments were conducted in a plant nursery, under a completely randomized experimental design consisting of six concentrations of IBA (0, 1000, 2000, 3000, 4000 and 5000 mg.kg-1 in industrial talc), four replications, and ten cuttings per plot. The stem cutting experiment also evaluated the effect of the types of cuttings (tanchan, basal, stratified basal, medial, and apical), with the material being collected from a yellow mombin tree in full vegetative growth. The root cuttings were collected from a matrix plant in the stage of vegetative rest and cut into 15 cm length segments. After 120 days, the following variables were evaluated: percentage of living, sprouted, rooted, and calloused cuttings, and dry mass of roots and sprouts. The cuttings of the tanchan type showed higher survival and sprouting percentages, regardless of the concentration of IBA applied, whereas the rooting rate was low. The application of IBA increased the rooting percentage of the root cuttings until the maximum concentration of 5000 mg.kg-1, reaching 77.5%, although it did not influence the other variables analyzed. The root cuttings of yellow mombin exhibit good regeneration capacity.